15.5k views
1 vote
Help ASAP

Which of the following correctly simplifies the expression 2 to the power of 2 multiplied by 6 to the power of 0 whole over 7, the whole cubed.? (5 points)

Question 4 options:

1)

2 to the power of 2 multiplied by 1 whole over 7, the whole cubed. = 2 to the power of 5 multiplied by 1 cubed over 7 cubed. = 32 over 343.

2)

2 to the power of 2 multiplied by 0 whole over 7, the whole cubed. = 2 to the power of 6 multiplied by 0 over 7 cubed. = 0

3)

2 to the power of 2 multiplied by 1 whole over 7, the whole cubed. = 2 to the power of 6 multiplied by 1 cubed over 7 cubed. = 64 over 343.

4)

2 to the power of 2 multiplied by 0 whole over 7, the whole cubed. = 2 to the power of 5 multiplied by 0 over 7 cubed. = 0

User Beyazid
by
5.7k points

1 Answer

7 votes

Answer:

(2^2 * 6^0) / 7)^3 =

(2^6 * 1^3) / 7^3 =

(64 * 1) / 343 =

64/343

Explanation:

I hope this helps!

User Alfetopito
by
6.4k points